Consumer Protection in Labeling of Foods Produced from Plants Genetically Modified by The New Genomic Techniques (NGTs) - Panichying, Theppharat; Piboon, Sutatip; Wanchum, Tanakrid; Detturatat, Benjaporn (Nitipat NIDA Law Journal, 2024)
The European Parliament voted to ease the regulation of plants genetically modified by the New Genomic Techniques (NGTs), categorizing those created with the Genome Editing (GEd) under the ‘NGT-1’ classification, which is treated similarly to conventional plants. While these plants are considered safer for consumer health compared to Genetically Modified Organisms (GMOs), there is no scientific evidence to definitively confirm this. Consequently, the European Parliament decided that NGT-1 labeling for food derived from plants must still be implemented to provide consumers with relevant information. This article aims to study consumer protection measures concerning the labeling of foods derived from plants (NGTs), bred using GEd, in categories NGT-1 and NGT-2. It conducts a comparative analysis of principles and legal frameworks related to consumer protection, food safety, and labeling in the European Union and Thailand. According to the study, it can be concluded that Thailand still lacks specific laws governing the control and supervision of NGT (GMOs/GEd) plants. Under consumer protection laws, the Committee on Labels should include NGT plants, whether imported or domestically produced, on the list of label-controlled products. Currently, the FDA requires labeling only for GMO foods; however, this regulation should be expanded to include all NGT-derived foods. Furthermore, the contamination threshold should be reduced from the current 5% to align more closely with the European Union’s 1% standard.